Identifying swimmers as water-polo or swim team-mates from visual displays of less than one second - Steel, K. A.; Adams, R. D.; Canning, C. G. (Journal of Sports Sciences, 2007)
Opportunities for ball passing in water-polo may be brief and the decision to pass only informed by minimal visual input. Since researchers using point light displays have shown that the walking or running gait of familiars can be identified, water-polo players may have the ability to recognize team-mates from their swimming gait. To test this hypothesis, members of a water-polo team and a competition swim team viewed two randomized sets of video clips, each less than one second long, of swimmers from both teams sprinting freestyle past a fixed camera. The arm stroke clip sequence showed only the upper body, and the kick sequence showed only the lower body. After viewing each video clip, observers rated their level of certainty as to whether the swimmer presented was a team-mate or not. Discrimination was significantly above chance in both groups. Water-polo players were better able to identify team-mates from their kick, whereas swimmers were better able to do so by viewing arm stroke. Our results suggest that, as with walking and running gait, small amounts of visual information about swimmers can be used for recognition, and so raise the possibility that specific training may be able to improve team-mate classification in water-polo, particularly in newly formed teams.